Corticosterone Preexposure Increases NF-κB Translocation and Sensitizes IL-1β Responses in BV2 Microglia-Like Cells - Liu, JiaJun; Mustafa, Sanam; Barratt, Daniel Thomas; Hutchinson, Mark Rowland (Frontiers in Immunology, 2018)
Corticosterone (CORT), a critical mediator of the hypothalamus pituitary adrenal axis in rodents, is a stress hormone that is classically viewed as possessing immune suppressive properties. CORT is now appreciated to also mediate the neuroimmune priming effect of stress to innate immune stimulation, and hence serves as a mechanistic link to the neuroimmune involvement in stress-related disorders. However, these dichotomous actions of CORT remain poorly defined. This study investigated the conditions and concentration dependency of CORT’s actions required to prime the innate immune system. Here we measured the effect of CORT pre-treatment on the downstream pro-inflammatory responses of BV2 mouse microglia-like cells stimulated by lipopolysaccharide (LPS). We quantified the concentration dependent CORT-mediated attenuation and enhancement of LPS stimulated inflammatory response. A high physiological concentration (500 nM) of CORT attenuated LPS-induced inflammatory IL-1β cytokine production in a glucocorticoid receptor dependent manner. However, a low concentration (50 nM) of CORT increased expression and release of IL-1β in a mineralocorticoid receptor (MR) dependent manner, with accompanied increases in NF-B translocation and changes to related gene transcription. These results suggest that a mild elevation in CORT may cause selective adaptations in microglia-like cells to over-respond to a second immune challenge in a non-classical manner, thus partially explaining both pro- and anti-inflammatory effects of CORT reported in the literature.